Update on the Diagnosis and Anticoagulant Treatment of the Antiphospholipid Syndrome - Nicoletta Riva; Alex Gatt (European Medical Journal Rheumatology, 2019)
Antiphospholipid syndrome (APS) is an acquired form of thrombophilia characterised by the presence of antiphospholipid antibodies and arterial/venous thrombosis or obstetric complications. Although antiphospholipid antibodies are reported in 1–5% of the general population, only a minority of these individuals will develop the clinical manifestations of APS. The typical expressions of APS are thrombotic events that can involve veins, arteries, or small vessels in any organ or tissue. Pregnancy morbidity refers mainly to early and late fetal loss, but pre-eclampsia, eclampsia, or placental insufficiency can also occur. Extra-criteria manifestations include thrombocytopenia, APS-associated nephropathy, valvular heart disease, neurological manifestations, and livedo reticularis. The diagnosis of APS is currently based on the Sydney criteria: i.e., meeting at least one clinical criterion (vascular thrombosis or pregnancy morbidity) and one laboratory criterion (lupus anticoagulant, anticardiolipin antibodies, or anti-β2 glycoprotein-I antibodies). Anticoagulation with unfractionated or low molecular weight heparin followed by vitamin K antagonist is the standard treatment for APS patients presenting with venous thromboembolism. There is not enough evidence regarding the use of the direct oral anticoagulants in this population. Patients presenting with arterial thrombosis may receive a combination of vitamin K antagonists and low-dose aspirin. In women with obstetrical APS, the combination of low molecular weight heparin and low-dose aspirin is usually prescribed to prevent pregnancy complications. The aim of this narrative review is to summarise the latest evidence on the diagnosis and antithrombotic treatment of APS.